Analisis Presrektif Guru terhadap Kebutuhan materi Reading Siswa Kelas XII Sekolah Menengah Kejuruan (SMK) Teknik Otomotif untuk Menghadapi Ujian Nasional - Anita Budi Rahayu (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2021)
Abstract: The purpose of this study was to find out the material needs of reading students in grade XII Vocational High School (SMK) automotive engineering to face the National Examination based on the teacher's perspective. This research was motivated by the evaluation of the development of the curriculum of the Vocational High School (SMK) of automotive engineering and the determination of the need for strengthening reading materials to face the National Examination. This research is qualitative descriptive research on needs analysis. To obtain data researchers gave questionnaires and conducted interviews with 4 teachers of grade XII SMK Automotive Engineering from the Smk English Teachers Group (KKG) Working forum. Furthermore, the results of questionnaires and interviews were used as the main data in this study. The result of this research is that according to the teacher's perspective students need mastery of reading in the understanding of grammar, function, main ideas, and text meaning to face the National Examination. Furthermore, the findings were followed up by teachers applying several reading learning strategies in the classroom such as by interpreting, guessing, & analyzing text grammatically with varied reading styles, to gain an understanding of the meaning of the text